A Retrospective Analysis of Universal Health Insurance Policy‐Making Process in Iran: A Qualitative Study - Mohammad Javad Kabir; Alireza Heidari; Mansoureh Lotfi; Zahra Khatirnamani; Reza Golpira (Health Science Reports, 2024)
ABSTRACT Background and Aims Universal Health Insurance (UHI) coverage began in 2014, after the implementation Health Transformation Plan (HTP) to reduce out‐of‐pocket payments and improve access to health services in Iran Health Insurance Organization (IHIO). The purpose of this study was to analyze the UHI policy‐making process in Iran. Methods This study was performed using Walt and Gilson's (1994) policy triangle framework and Kingdon's multiple streams model. Data were collected through document review, in‐depth individual interviews (constituting 17 policymakers and top, middle, and operational level managers), and one round‐table discussion (constituting 10 top managers and senior policymakers). The majority of the participants were MD and MPH (47.07%). Document review data were analyzed using thematic content analysis. Interviews and discussions were analyzed using framework analysis. Results The high‐level documents of Iran emphasize the need for insurance coverage. The commitment of the new government to enforce the laws, concurrent implementation of the UHI and the HTP, the new government's approach to enforcing civil rights, and media pressure to speed up the implementation process. UHI was initiated in 2014 and about 11 million people across the country were covered by free health insurance but the budget did not change in proportion to the increase in insured population, and increased IHIO's debt to contracting centers. Conclusions To achieve continuity and effectiveness of UHI in Iran, all stakeholders should be involved. Political will and commitment and sustainable financing are needed for it.